A novel δ-MnO2 with carbon nanotubes nanocomposite as an enzyme-free sensor for hydrogen peroxide electrosensing. Issue 56 (24th May 2016) - Begum, Halima; Ahmed, Mohammad Shamsuddin; Jeon, Seungwon
Abstract : We have reported the synthesis and application of carbon nanotubes supported δ-MnO2 (δ-MnO2 /CNTs) nanocomposite as enzyme-free sensor for the detection of H2 O2, where δ-MnO2 serves as the catalytic center and CNTs as the highly conductive base. Abstract : We have reported the synthesis and application of a δ-MnO2 with carbon nanotubes (δ-MnO2 /CNTs) nanocomposite as an enzyme-free sensor for the detection of H2 O2 through an electroreduction reaction, where δ-MnO2 serves as the catalytic center and CNTs as the highly conductive base material. The δ-MnO2 /CNTs nanocomposite was synthesized via a simple and single-step hydrothermal process in alkaline solution without using any surfactants or templates. The electrochemical properties of the δ-MnO2 /CNTs on a glassy carbon electrode were investigated by cyclic voltammetry, and amperometry. It was found that, under optimized conditions, the sensor fabricated electrode provides linear amperometric responses for H2 O2 in a large concentration range from 0.05 to 22 mM and a detection limit of 1 μM with a comparatively high sensitivity of 243.9 μA mM −1 cm −2 . In addition, the δ-MnO2 /CNTs modified GCE exhibits excellent selectivity, and good reproducibility for H2 O2 detection. It is promising that the proposed H2 O2 sensor can be used as an effective tool to measure the H2 O2 in practical samples.